Expression of EpCAM and prognosis in early‐stage glottic cancer treated by radiotherapy. (14th July 2014) - Murakami, Naoya; Mori, Taisuke; Yoshimoto, Seiichi; Ito, Yoshinori; Kobayashi, Kazuma; Ken, Harada; Kitaguchi, Mayuka; Sekii, Shuhei; Takahashi, Kana; Yoshio, Kotaro; Inaba, Koji; Morota, Madoka; et al.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Treatment of head and neck squamous cell carcinoma (HNSCC) often requires radiotherapy, but relapse can occur. There is, therefore, an urgent need for the identification of a predictive novel biomarker for radiosensitivity. The epithelial cell adhesion molecule (EpCAM) has been shown to promote the transformation of malignant tumors, and EpCAM may have prognostic significance, but it is not known if EpCAM determines prognosis, especially with respect to radiotherapy. Therefore, we determined the incidence of the expression of EpCAM in HNSCC and analyzed the prognostic value in patients with early‐stage glottic cancer treated with radiotherapy. Study Design Retrospective analysis. Methods All patients with HNSCCs examined in our hospital between January 2012 and February 2013 were analyzed prospectively for the expression of EpCAM. T1–2N0 glottic cancer patients who were primarily treated by radiation therapy between 1995 and 2008 were retrospectively investigated. Patients with or without local recurrence after radical radiation therapy were extracted. The relationship between local recurrence and histopathologic EpCAM expression was compared within these two groups. Results One hundred eighteen patients with HNSCCs from the nasopharynx, oropharynx, hypopharynx, larynx, oral cavity, paranasal cavity, unknown primary, and other sites were analyzed. Positive expression of EpCAM was noted in the oropharynx, hypopharynx, and larynx (72%, 90%, and 58%, respectively). Seventeen and 22 patients with or without local recurrence were extracted, respectively. There was no difference between two groups, with the exception of EpCAM expression. Conclusions The expression of EpCAM in HNSCC was investigated. Patients with strong EpCAM expression were associated with local recurrence after primary radiation therapy. Level of Evidence NA Laryngoscope, 124:E431–E436, 2014